The evaluation of mandibular bone density in chronic periodontitis models - Yuliana Mahdiyah Da’at Arina; F. Ferdiansyah; Mohamad Rubianto (Dental Journal (Majalah Kedokteran Gigi), 2018)
Background: Bone density, an important factor in functional bone quality, can affect the success of implant osteointegration or orthodontic treatment. A number of studies report that chonic periodontitis constitutes one risk factor of osteoporosis characterized by low bone mineral density and that the mandible is susceptible to osteoporosis. Purpose: The purpose of this study was to evaluate mandibular bone density in animal subjects suffering from chronic periodontitis. Methods: 40 male Wistar rats were divided into four chronic periodontitis groups and four control groups (each group n=5). As chronic periodontitis models, the subjects were injected with 2×109 CFU/ml of Porphyromonas gingivalis in the sulcular gingiva, whereas control group members were injected with normal saline. After 2, 3, 4 and 6-week injection periods, the subjects were sacrificed and radiographic examination of the mandibular bone subsequently performed. Mandibular bone density was evaluated by histometric analysis. Results: The mandibular bone density in members of the chronic periodontitis group was significantly lower than those of the control group (p<0.05). The reduced mandibular bone density in the chronic periodontitis group was in line with the protracted bouts of periodontitis. Conclusion: Reduced mandibular bone density was found in the chronic periodontitis model. The longer the duration of a bout of chronic periodontitis, the greater the reduction in mandibular bone density.